An integrated natural gas power cycle using hydrogen and carbon fuel cells. (1st December 2017) - Zhuang, Quan; Geddis, Philip; Runstedtler, Allan; Clements, Bruce
Highlights: An advanced natural gas dual fuel cell system is proposed. Natural gas decarbonisation followed by a hydrogen fuel cell and a carbon fuel cell. Anode exhaust from carbon fuel cell is a pure CO2, ready for sequestration. The power cycle has an efficiency of 61% (HHV of natural gas) with 82% carbon capture. Abstract: An integrated power cycle comprising natural gas decarbonization in conjunction with a hydrogen fuel cell and a carbon fuel cell is proposed, termed a natural gas decarbonization dual fuel cell system (NGDDFC). In this process hydrogen and solid carbon produced in a natural gas decarbonization step are fed to hydrogen and carbon fuel cells, respectively. A pure carbon dioxide stream is produced from the carbon fuel cell, suitable for sequestration. Process modeling of this cycle carried out using UniSim R430, for the non-CO2 capture case, showed a cycle power efficiency of about 61%, which is 15 percentage points higher than the current natural gas combined cycle (NGCC) case. With 82% CO2 capture, the NGDDFC had a net efficiency about 20 percentage points higher than the published NGCC option, albeit with a slightly lower capture percentage (82% vs. 90%).